Pengaruh Experiential Marketing Terhadap Kepuasan Pengguna Smartphone Blackberry Curve (Studi Pada Mahasiswa Fakultas Ekonomi Universitas Trunojoyo Madura) - Samsul Bahri; Bambang Setiyo Pambudi; Fathor Fathor (Jurnal Studi Manajemen dan Bisnis, 2014)
The purposes of this study are; (1) to determine the influence of experential Marketing consisting of sense, feel, think, act and relate on customers’ satisfaction, (2) to determine the dominant influence of Experential Marketing variable on Blackberry Curve smartphone customers’ satisfaction.Research approach used is quantitative, means that it is a positivism philosophy study of which purpose is testing the hypothesis set. Sample used in this study is Blackberry Curve smartphone customer as 60 respondents who are students of Economic Faculty, University of Trunojoyo Madura. Samples collecting method applied is purposive sampling. Reliability and validity test are used as the instrument testing, while data analysis technique applied for hypothesis testing is descriptive and multiple linear regressions analysis by involving F tes ( simultaneous) and t test (partial). The results of study show that the adjusted R Squarevalue is 0,815. It means the amount influence of independent to dependent variable is 81,5%, while the remaining of 18,5% is influenced by another variable outside of this study. Based on F Experiential Marketing consisting of sense, feel, think, act, dan relatesimultaneously and significantly influence the Blackberry Curve smartphone customers’ satisfaction. Similarly, the t test results the Experiential Marketing consisting of sense, feel, think, and act has significant influence on Blackberry Curve smartphone customers’ satisfaction, but only the relate that does not have significant influence. The dominant influence is feel variable.